2014
DOI: 10.1186/1478-7954-12-12
|View full text |Cite
|
Sign up to set email alerts
|

Detecting type 2 diabetes and prediabetes among asymptomatic adults in the United States: modeling American Diabetes Association versus US Preventive Services Task Force diabetes screening guidelines

Abstract: BackgroundScreening to detect prediabetes and diabetes enables early prevention and intervention. This study describes the number and characteristics of asymptomatic, undiagnosed adults in the United States who could be detected with prediabetes and type 2 diabetes using the American Diabetes Association (ADA) guidelines compared to the United States Preventive Services Task Force (USPSTF) guidelines.MethodsWe developed predictive models for undiagnosed diabetes and prediabetes using polytomous logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 26 publications
1
49
0
3
Order By: Relevance
“…44 Applied to the 2012 estimate of 86 million with prediabetes, this suggests that potentially 26À37 million case patients in 2012 could have been detected and enrolled in treatment.…”
Section: Resultsmentioning
confidence: 97%
“…44 Applied to the 2012 estimate of 86 million with prediabetes, this suggests that potentially 26À37 million case patients in 2012 could have been detected and enrolled in treatment.…”
Section: Resultsmentioning
confidence: 97%
“…14,15 In 2008 the USPSTF revised its guidelines to recommend sulted in many cases of undiagnosed diabetes being missed, and did not provide direction on diabetes prevention via prediabetes. 16,17 In October 2015, 4 months before data collection for this survey, the USPSTF revised its guidelines to recommend screening for prediabetes, thereby having both the ADA and the USPSTF recommending screening for prediabetes. 3 The results of this study showed that respondents who were less positive in their attitudes toward prediabetes were less likely to say that they followed national guidelines on diabetes prevention.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the latest UK modelling suggests that only 25% of those with diabetes are now undiagnosed [22], half of the 50% quoted historically. This Treating hyperglycaemia in type 2 diabetes from diagnosis reduces micro-and macrovascular outcomes and mortality over 10 years [14] Managing IFG/IGT reduces progression to type 2 diabetes over 15 years [18] Intensive management of screen-detected diabetes reduces incidence of cardiovascular events and death over 5 years in the UK [11] In the Ely trial, testing for diabetes using an OGTT with repeated OGTT after 5 years was associated with non-significant reductions in all-cause mortality, significantly lower ABPI and non-significantly reduced rates of retinopathy in those in the screening group who were diagnosed with diabetes vs unscreened individuals [5,6] In the 2015 US Preventive Services Task Force systematic review, all seven health economic modelling studies reported screening (vs no screening) at age 40-45 is associated with incremental cost-effectiveness ratios of < $15,000/quality-adjusted life year (QALY), which is well under the traditional thresholds for cost-effectiveness [3] Lessons from diabetes screening studies 1 2 4 5 3 is likely to be the result of opportunistic screening in primary care. These developments increasingly suggest that both policy makers and primary care practitioners believe that equipoise has now been reached for screening for undiagnosed diabetes, and the only questions that remain are who and how to screen.…”
Section: Designing Future Trials Of Diabetes Screeningmentioning
confidence: 99%
“…Evidence from diabetes screening studies A systematic review in 2014, to update the 2008 US Preventive Services Task Force recommendations [3], concluded that, while treatment for impaired fasting glucose (IFG)/impaired glucose tolerance (IGT) delayed progression to (type 2) diabetes, screening for diabetes did not improve mortality rates. This conclusion was based upon two studies: (1) the Anglo-Danish-Dutch study of intensive treatment in people with screen-detected diabetes in primary care (ADDITION)-Cambridge trial (n = 16,047; high risk men and women, aged 40-69 years; 10 year duration) [4], with a mortality HR of 1.06 (95% CI 0.90, 1.25); and (2) the Ely trial (n = 4936; all men and women aged 40-65 years; 18 year duration) [5] .…”
Section: Introductionmentioning
confidence: 99%